THE EFFECT OF USE MIXED FERMENTATION CASSAVA PALM KERNEL CAKE AND FEED WITH ADDING MORINDA CITRIFOLIA OF THE FULL BROILER ON PERCENTAGE OF CARCASS, PERCENTAGE OF FAT ABDOMINAL, FAT CONTENT OF MEAT AND POWER LOSSES MEAT - Goo, Agustinus (Universitas Kanjuruhan Malang, 2014)
The experiment was conducted on November 01, 2013 to December 02, 2013 at the Laboratory in University of Kanjuruhan Malang. The purpose of this study to determining the effect of the use of mixtures of fermented palm kernel cake and cassava, with the adding Morinda citrifolia in complete feed on broiler carcass percentage, fat abdominal percentage, fat and power losses meat. The method used the method of experiment using a completely randomized design with factorial pattern consisting of 8 treatments with 3 replications. Each replication consisted of 4 chickens using fermented feed treatments 0%, 10%, 20%, 30% without the adding Morinda citrifolia and fermented feed treatments 0%, 10%, 20%, 30% with the adding Morinda citrifolia. The variables observed in this study are the percentage of carcass, fat abdominal percentage, fat meat and power losses meat. The results showed the effect of using a mixture of fermented palm kernel cake and cassava in broiler complete feed with the adding Morinda citrifolia was highly significant (P <0.01) on fat content of meat. While the effect of the use of mixtures of fermented palm kernel cake and cassava in broiler feed complete with the adding Morinda citrifolia no significant effect (P> 0.05) on carcass percentage, fat abdominal percentage and power losses meat. From the results of this study concluded the effect of using a mixture of fermented palm kernel cake and cassava in broiler complete feed with the adding of Morinda citrifolia very significant effect on the fat content of meat with the highest value (74.43%). While not a significant effect on carcass percentage, abdominal fat percentage and and power losses meat. suggested to the farmers that the proportion of feeding fermented palm kernel cake and cassava with the addition of Morinda citrifolia in broiler complete feed granting enhanced level above 30%.Keywords: Fermentation, Broiler Complete Feed, Fat, And Meat Shrinkage Power